A crucial step towards a safer healthcare system: embracing the WHO surgery checklist in Pakistan - Khan, Abdullah; Yousaf, Mirza Rehan; Naeem, Hamza (Journal of the Pakistan Medical Association, 2024)
Mistakes happen. We all make mistakes that makes us human. But when a surgeon makes mistake, it costs lives. Being surgeon, a little negligence might make catastrophic incidents happen. An unintentionally retained needle in the abdominal cavity or surgery of a normal limb instead of faulty gall bladder can have serious consequences not only for the patient and the patient-physician relation but also for the healthcare system. Such negligence events have become common in Pakistan. In Faisalabad, it was reported that a patient with gall stones was mixed up with a patient of limb surgery having the same name that led to inappropriate surgical procedures performed on both.[1] In Abbottabad, an incident was reported where the patient had to undergo an arm surgery but an eye surgery was performed in a private hospital. [2] Everyone blamed the surgeon and the health care system but no one dared to dig into the cause. Why are such childish mistakes happening? And if happened once how is this being repeated? How could a surgeon, a practically learned man make such non-sense? The answer to all these questions lies in the WHO Surgical Safety Checklist. “Safe Surgery Save Lives” was initiated by the World Health Organization (WHO) in 2007 in order to alleviate the number of such unwanted events encountered in the surgical procedures. For the purpose of improving patient safety with least of the resource utilization, WHO came on board with safety checklist in 2008.[3] The WHO 19-item checklist is based on advocating safety checks and a good communication among surgery team members during perioperative periods. It also contains a time-out procedure. In Pakistan, in spite of the great effectiveness, the time-out is either not practiced or is done by some junior, and not by the operating surgeon at the preoperative time. A time-out is a short interval before incision during which it is confirmed that the patient on the surgery bed is the correct one, the procedure to be performed on it is exact and at the required part of body either marked or unmarked.[4] The surgeon should be present at the time-out and all members should guarantee the correct patient, procedure and site. Patient participation in the time-out process is also advised. Majority of the patients show great compliance and satisfaction for participating in the time-out procedure. —Continue